Manajemen Program Siaran Pemberitaan Radio Republik Indonesia dalam Penyampaian Informasi Kepada Publik - Ririn Febrianti; Uus Uswatusolihah (IAIN Madura, 2025)
This study aims to analyze the management of news broadcasting programs at Radio Republik Indonesia (RRI) Purwokerto in delivering information to the public. Using a qualitative method with an ethnographic approach, data were collected through observation, interviews, documentation, and literature review. The findings reveal that program management involves theme planning, guest selection, rundown preparation, and presenting news in various formats, such as interactive dialogues, field reports, and talk shows. RRI Purwokerto faces several challenges, including limited human resources and competition from digital media, yet addresses these issues by optimizing digital platforms and improving staff competency. More specifically, the study reveals that the implementation of program management directly contributes to enhancing the quality of public information delivery, making it more factual and easier for audiences to understand.